Present and future biodiversity risks from fossil fuel exploitation. Issue 4 (2nd April 2018) - Harfoot, Michael B. J.; Tittensor, Derek P.; Knight, Sarah; Arnell, Andrew P.; Blyth, Simon; Brooks, Sharon; Butchart, Stuart H. M.; Hutton, Jon; Jones, Matthew I.; Kapos, Valerie; Scharlemann, Jӧrn P.W.; Burgess, Neil D.
Abstract: Currently, human society is predominantly powered by fossil fuels—coal, oil, and natural gas—yet also ultimately depends on goods and services provided by biodiversity. Fossil fuel extraction impacts biodiversity indirectly through climate change and by increasing accessibility, and directly through habitat loss and pollution. In contrast to the indirect effects, quantification of the direct impacts has been relatively neglected. To address this, we analyze the potential threat to >37, 000 species and >190, 000 protected areas globally from the locations of present and future fossil fuel extraction in marine and terrestrial environments. Sites that are currently exploited have higher species richness and endemism than unexploited sites, whereas known future hydrocarbon activities will predominantly move into less biodiverse locations. We identify 181 "high‐risk" locations where oil or gas extraction suitability coincides with biodiversity importance, making conflicts between extraction and conservation probable. In total, protected areas are located on $3‐15 trillion of unexploited hydrocarbon reserves, posing challenges and potentially opportunities for protected area management and sustainable financing.